Geographic variation in the pollen of Silene latifolia (S. alba, S. pratensis) : a quantitative morphological analysis of population data. - Prentice, H. C. ; 0000-0003-2548-0525; Mastenbroek, O.; Berendsen, W.; Hogeweg, P. (Canadian Journal of Botany, 1984)
There is a geographic separation of the 2 pollen morphs in European Silene latifolia, with the changeover zone running NW-SE from the Netherlands to Greece. Reticulate grains are characteristic of western populations, microechinate grains of eastern populations. -from AuthorsDept of Population & Evol Biol, Univ of Utrecht, Padualaan 8, 3584 CH Utrecht, The Netherlands.